Assistance in Making Digital Learning Media Based on Ubiquitous Learning in Implementing The Independent Curriculum in Madrasah Ibtidaiyah Cililin Sub-District - Rizkia Muhammad, Fikri; Saepulloh (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
The implementation of Merdeka Curriculum demands innovation in the learning process, one of which is through the use of digital learning media based on ubiquitous learning (u-learning). U-learning allows learning to take place anytime and anywhere, supporting flexibility in meeting student needs. This research aims to assist Madrasah Ibtidaiyah teachers in Cililin Sub-district in designing and applying u-learning-based digital learning media relevant to the Merdeka Curriculum. The method used is a participatory approach, involving training, workshops and direct assistance to teachers. The mentoring results show that teachers are able to develop digital learning media using platforms. They also successfully integrated elements of the Merdeka Curriculum, such as project-based learning and differentiation, into the designed media. In addition, the utilization of digital technology increases student engagement in learning, both in class and independently. Teachers feel more confident in utilizing technology and show increased creativity in compiling learning materials. This study concludes that assistance in making u-learning-based digital learning media is effective in supporting the implementation of Merdeka Curriculum in Madrasah Ibtidaiyah. The main recommendation is the need for continuous training to ensure teachers can utilize technology optimally, as well as the provision of supporting infrastructure such as an adequate internet network. With this approach, it is expected that learning in madrasah can be more innovative, inclusive, and relevant to the needs of students in the digital era.